Genetic, Phenotypic and Metabolic Diversity of Yeasts From Wheat Flag Leaves - Gouka, Linda; Vogels, Caroline; Hansen, Lars H.; Raaijmakers, Jos M.; Cordovez, Viviane (Frontiers in Plant Science, 2022)
The phyllosphere, the aboveground part of a plant, is a harsh environment with diverse abiotic and biotic stresses, including oscillating nutrient availability and temperature as well as exposure to UV radiation. Microbial colonization of this dynamic environment requires specific adaptive traits, including tolerance to fluctuating temperatures, the production of secondary metabolites and pigments to successfully compete with other microorganisms and to withstand abiotic stresses. Here, we isolated 175 yeasts, comprising 15 different genera, from the wheat flag leaf and characterized a selection of these for various adaptive traits such as substrate utilization, tolerance to different temperatures, biofilm formation, and antagonism toward the fungal leaf pathogen Fusarium graminearum. Collectively our results revealed that the wheat flag leaf is a rich resource of taxonomically and phenotypically diverse yeast genera that exhibit various traits that can contribute to survival in the harsh phyllosphere environment.